Evaluation of the speed of a complex visual-motor response in highly skilled female boxers - Korobeynikov, G.; Shtanagey, D.; Ieremenko, N.; Aksiutin, V.; Danko, T.; Danko, G.; Goletc, A.; Korobeynikova, L.; Maximovich, N.; Dudorova, L.; Kolumbet, A. (Journal of Physical Education and Sport, 2020)
Purpose:- determining the peculiarities of complex visual-motor response of female boxers with different types of functional asymmetry. Material: 50 highly skilled female boxers (masters of sports of international class, masters of sports). The study of female boxer psychomotor functions was designed according to a certain scheme. The motor component of motor response was examined by means of tapping test. The time of a simple and two complex visual-motor responses was determined. The study was completed by determining the identification time for visual stimuli of various degrees of complexity without a motor response. It was assumed that this will allow to consider the visual-gnostic component in a "pure" form. Such a design of the study permitted to evaluate the contribution of each component of psychomotor response to the response speed of female boxers with different types of functional hemispheric asymmetry (FHA) profile. Results:the right hand of the right-handers was found to be significantly faster than that of left-handers and, especially, ambidexters. The left hand speed of the right-handers is almost the same as that of the left-handers, whereas in ambidexters it is significantly higher. The right-handers appear to be faster during realization of complex visual-motor response than both the left-handers and ambidexters. As for the asymmetry of the legs, it is not possible to talk about the relationship between the lateralization character and the speed of the choice time. Among most of athletes the right-legged (60.0%) and the left-legged (75.0%) were in the group with a high speed of response. Conclusions:A comparison of the responses to the stimulus of the two alternatives shows that the right hand of right-handers is significantly faster than that of the left-handers and, especially, ambidexters. The speed of the left hand of the right-handers is almost the same as that of the left hand of the left-handers, and only in ambidexters it is much higher. Comparison of the responses to the stimulus of the three alternatives indicates that both the right hand and the left hand of the right-handers are significantly faster than those of athletes of the other two groups.Right-handers tend to be faster than left-handers and ambidexters during realization of a complex visual-motor response. The time of complex response in highly skilled female boxers is associated with visual lateralization. Athletes with the right dominant eye are more "speedy".